Time-triggered stream scheduling method combining no-wait and time-slot mapping reuse - HE Qian; GUO Yanan; ZHAO Baokang; PAN Qi; WANG Yong (Tongxin xuebao)
The proper functioning of numerous applications in industrial control systems relies on deterministic and low-latency network transmission, driving the development of time-sensitive networking. To guarantee the deterministic stream transmission in industrial control systems, a time-triggered stream scheduling method combining no-wait and time-slot mapping reuse (NW-TSMR) was proposed. Firstly, the time-sensitive network communication elements of industrial control systems were modeled, and by analyzing the characteristics of time-triggered streams, several constraints such as link, stream transmission, stream isolation, and frame isolation were simplified. The base period was used as the scheduling cycle time, by adopting no-wait scheduling for real-time streams and time-slot mapping reuse for cyclic streams, the length of gate control list was reduced. Then, a conflict detection method that utilized the midpoint of the data frame transmission interval significantly reduced the time complexity associated with slot conflict detection. Finally, several time-triggered stream scheduling optimization functions were given and solved based on an improved multi-objective genetic algorithm. The correctness and feasibility of NW-TSMR is verified through experiments, and the average gate control list length is reduced by 59.7%.